CBX4 regulation of senescence and associated diseases: Molecular pathways and mechanisms - Qianxing Hu; Linming Su; Wanli Zhao; Yinuo Jin; Liang Jin; Yue Yang; Fangfang Zhang (Pharmacological Research)
Polycomb repressive complex 1 (PRC1) is a multisubunit, evolutionarily conserved epigenetic regulator critical to numerous biological processes. Being a core component of the canonical PRC1 subunit within the Polycomb group protein complex, Chromobox4 (CBX4), a SUMO E3 ligase, can bind to H3K27me3 and recruit PRC1. This ligase regulates the SUMOylation of various proteins and permits their post-translational modification under different physiological conditions. CBX4 has been reported to regulate the development of senescence and various diseases in vivo. This review delves into the physiological functions and action mechanisms of CBX4 across different tissues and cells, particularly focusing on its primarily roles in migration, cellular senescence, metabolic dysregulation, inflammation development, and tumor proliferation. Targeting CBX4 offers a therapeutic potential for delaying cell senescence and suppressing tumor growth.